2000
DOI: 10.1097/00000539-200008000-00030
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Epidural Infusions of Levobupivacaine With and Without Clonidine for Postoperative Pain Relief in Patients Undergoing Total Hip Replacement

Abstract: In patients undergoing total hip replacement, the addition of the alpha(2)-adrenergic agonist clonidine to epidural infusions of levobupivacaine significantly improved postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 6 publications
2
23
0
2
Order By: Relevance
“…11 In this study both the groups were comparable with regard to age, duration of surgery. Clonidine combined with levobupivacaine has a faster onset of sensory and motor block which was in accordance with Milligan KR et al 12 , Gupta S et al 13 and Jain A et al 14 Clonidine being a lipophilic drug is rapidly absorbed into the spinal compartment and blocks the conduction of C and Aδ fibres. 15 Chalkiadis DS et al 16 in their study demonstrated the absorption characteristics of epidural levobupivacaine with clonidine and adrenaline via caudal epidural route and showed that clonidine mixed with levobupivacaine had a faster absorption compared to adrenaline mixed with levobupivacaine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…11 In this study both the groups were comparable with regard to age, duration of surgery. Clonidine combined with levobupivacaine has a faster onset of sensory and motor block which was in accordance with Milligan KR et al 12 , Gupta S et al 13 and Jain A et al 14 Clonidine being a lipophilic drug is rapidly absorbed into the spinal compartment and blocks the conduction of C and Aδ fibres. 15 Chalkiadis DS et al 16 in their study demonstrated the absorption characteristics of epidural levobupivacaine with clonidine and adrenaline via caudal epidural route and showed that clonidine mixed with levobupivacaine had a faster absorption compared to adrenaline mixed with levobupivacaine.…”
Section: Discussionsupporting
confidence: 79%
“…Alves TCA and BrazJRC 17 also showed a significant lower VAS score compared to the control group. However Milligan Kr et al 12 demonstrated a lower VAS score in levobupivacaine with clonidine group but it was not statistically significant compared to the levobupivacaine only group.…”
mentioning
confidence: 90%
“…Blood pressure was significantly lower in the clonidine group over time but without clinical consequence. [11] Milligan et al opined that, in patients undergoing total hip replacement, the addition of the alpha(2)-adrenergic agonist clonidine to epidural infusions of levobupivacaine significantly improved postoperative analgesia [12] .…”
Section: Discussionmentioning
confidence: 99%
“…16 The quality of pain relief from low-dose epidural infusions of plain local anaesthetic consistently benefits from the addition of adjuvants such as opioids (Hubler et al, 2001, 25 Senard et al 2002 23 ) or alpha-2 adrenoceptor agonists. Potential dose-sparing benefits are more obvious for local anaesthetic side effects (hypotension and motor block) than for opioid-related side effects.…”
Section: Postoperative Analgesiamentioning
confidence: 99%